Jan Baudouin de Courtenay i Aleksander Brückner - Marek Łaziński (Ksiegarnia Akademicka Publishing, 2017)
Jan Baudouin de Courtenay and Aleksander Brückner The article presents the lives and mutual relations between two outstanding Polish scholars, professors of lingusistics and philology at universities in Russia and Germany at the end of the Partitions of Poland. Brückner in Berlin and Baudouin de Courtenay in Petersburg (earlier Kazan and Dorpat) can be considered amabssadors of Polish culture and research. The relations between them were a mixture of reverence and contempt, involving Baudouin’s students, Kruszewski and Ułaszyn who remained in conflict with Brückner. Their fate and the decisions made by both leading figures of Polish linguistics before, during and after the Great War of 1914–1918, show the difference in their approach to linguistic research and contemporary political issues.